Diglossia supportive language practice – On the separation of languages or the mixing of languages as the norm in the daily life of the Kindergarten in German-speaking Switzerland - Kassis-Filippakou, Maria; Panagiotopoulou, Argyro (Swiss Journal of Educational Research, 2018)
The following contribution focuses on the pedagogical quality of language support in the field of kindergarten education. The descriptive-analytical study considers curricular and diglossia constraints specific to Swiss German-speaking region. Our ethnographically orientated field study demonstrates that language support in its practical realization assumes and generates the mixing and the separation of languages. We discuss our results with respect to new social linguistically based educational and didactic insights which can focus on and contribute to the general linguistic repertoire of multilingual people (teachers and children), and thus could contribute to an increase in the quality of (pre-) school language teaching in German-speaking Switzerland.